Teacher Burnout in Fulfilling the Work Result Plan Filling Policy in the Baron Cluster, Sukoharjo Regency - Puspitasari, Elin; Habiby, Wahdan Najib (CV. Rayyan Dwi Bharata, 2024)
The policy of filling out the Work Results Plan (RHK) in the Baron Cluster, Sukoharjo Regency is one of the triggers for stress and burnout for teachers. This research aims to describe the factors that cause teacher burnout in fulfilling the RHK filling policy. This research uses qualitative field research. The data source was obtained from elementary school teachers who taught in the Baron Sukoharjo cluster. The data validity technique uses source triangulation techniques. Data collection techniques use interviews, observation and documentation. Data analysis techniques use data reduction, data presentation, data condensation, and drawing conclusions. The results of the research show that the factors that cause teacher burnout in fulfilling the policy of filling out work results plans (RHK) in the Baron Sukoharjo Cluster are excessive workload, a non-conducive work environment, and teachers' personal problems.